Renal-type clear cell carcinoma of the prostate: a rare case report - Xie, Hongjun; Chen, Jiaqi; Pei, Xinqi; Ma, Zhenkun; Liang, Liang; Yang, Zhao (Current problems in cancer. Case reports, 2025)
Renal-type clear cell carcinoma (RTCCC) of the prostate is an extremely rare histological variant of prostate cancer, with very few reported cases in the literature. It is characterized by cells with abundant clear cytoplasm and has an aggressive clinical course. In this report, we present a rare case of RTCCC of the prostate. We describe a 60-year-old male with a two-year history of urinary frequency, urgency, and dysuria, who was admitted to the hospital for benign prostatic hyperplasia. Ultrasound and magnetic resonance imaging (MRI) revealed prostate enlargement. The patient subsequently underwent transurethral resection of the prostate. A total of 150 g of tissue was resected, demonstrating morphological and immunohistochemical similarities to clear cell carcinoma of the kidney. A whole-body FDG PET/computed tomography (CT) scan did not detect any renal masses but showed significant uptake in the prostate, along with pelvic lymph node metastasis. The patient subsequently received radiation therapy. To the best of our knowledge, reports of clear cell carcinoma of the prostate are exceedingly rare.